Data on medicinal plants used by herbalists for boosting immunity in people living with HIV/ AIDS in Uganda - Anywar, Godwin; Kakudidi, Esezah; Byamukama, Robert; Mukonzo, Jackson; Schubert, Andreas; Oryem-Origa, Hannington (Elsevier, 2020)
This Data in Brief article provides supplementary information to orearlier Ethnobotanical survey on medicinal plants used by traditional medicine practitioners to boost the immune system in people living with HIV/AIDS in Uganda [1]. We identified 71 medicinal plant species from 37 families and 64 genera. The data were analysed using descriptive statistics such as frequencies and percentages. Most of the plant species used were trees (27) and herbs (25) from the Fabaceae (15.7%) Asteraceae Phyllanthaceae (8.6%),Rubiaceae (5.7%) and Rubiaceae (5.7%) families. Additionally, we conducted a detailed literature review of the documented species to justify their use as immunostimulants. This data is derived from a larger survey to document the use of medicinal plant species intreating opportunistic infections in Uganda by Anywar et al. [2].
Keywords: Medicinal plants; Immunostimulants; Immunity; Traditional medicine practitioners; Herbalists; HIV/AIDS